The Pericope Adulterae, the Gospel of John, and the literacy of Jesus - Keith, Chris. (New Testament Tools, Studies and Documents, 2009)
Although consistently overlooked or dismissed, John 8.6, 8 in the Pericope Adulterae is the only place in canonical or non-canonical Jesus tradition that portrays Jesus as writing. After establishing that John 8.6, 8 is indeed a claim that Jesus could write, this book offers a new interpretation and transmission history of the Pericope Adulterae . Not only did the pericope's interpolator place the story in John's Gospel in order to highlight the claim that Jesus could write, but he did so at John 7.53-8.11 as a result of carefully reading the Johannine narrative. The final chapter of the book proposes a plausible socio-historical context for the insertion of the story.